Instructors’ perceptions and pedagogical approaches to online teaching in selected Malaysian private universities - Heng, Jing Xiang; Lee, Kam-Fong; Amini, Mansour; Ravindran, Latha (Institute of Advanced Engineering and Science, 2024)
Private university instructors in Malaysia faced obstacles in their adaptation to the online learning mode while holding their pre-existing academic duties. This research aimed to explore those obstacles, and observe how the instructors tailored their pedagogical approaches. The research employed a qualitative research design. We used convenience sampling to select eight instructors from three private universities in Malaysia using semi-structured interviews. The findings revealed that the main challenges were instructors’ own workload and lessened time for professional development, the incompatibility of the provided multimedia with their teaching approaches, as well as the problem with their students’ readiness and participation. It was found that the instructors adapted their pedagogical approaches with a main focus on learners’ cognitive development, and this was hoped to be achieved through their choices of learning tools and multimedia, instructional strategies of collaborative and reflective learning, and consideration of learning outcomes and objectives. The instructors also incorporated their students’ feedback into their content development to increase the engagement. Interestingly, some instructors initiated their own content and approach, while receiving support from their institutes, peers, and other resources. The findings may contribute positively to instructor’s efforts in providing and maintaining an interactive, productive and stable learning environment.